The long-term costs of government surveillance: Insights from Stasi spying in East Germany - Andreas Lichter; Max Löffler; Sebastian Siegloch (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Despite the prevalence of government surveillance systems around the world, causal evidence on their social and economic consequences is lacking. Using county-level variation in the number of Stasi informers within Socialist East Germany during the 1980s and accounting for potential endogeneity, we show that more intense regional surveillance led to lower levels of trust and reduced social activity in post-reunification Germany. We also find substantial and long-lasting economic effects of Stasi spying, resulting in lower self-employment, higher unemployment and larger out-migration throughout the 1990s and 2000s. We further show that these effects are due to surveillance and not alternative mechanisms. We argue that our findings have important implications for contemporary surveillance systems.
Keywords: H11; N34; N44; P20; 330; government surveillance; trust; social ties; East Germany